PERANAN WANITA TANI TERHADAP PENERAPAN PROGRAM PENYULUH PERTANIAN - Sasmitha Siregar; Yudha Andriansyah Putra (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractResearch on the role of women farmers towards the implementation of agricultural extension program has been carried out using a simple random method (Simple Random Sampling). The results of hypothesis testing and calculation of Multiple Linear Regression Obtained by Multiple R value of 0.94 or 94%. Calculated F values obtained for 52.405 and table F value of 2.70. Then F calculated> F table, the 95% confidence level. The test results with the t test for age significantly influenced the implementation of agricultural extension program to calculate the t values obtained 2.215 and 1.71 t table (t count> t table). The test results with the t test for education does not significantly affect the implementation of agricultural extension program to calculate the t values obtained -4.360 and 1.71 t table (t calculated <t table). The test results with the t test for experience not significantly affect the implementation of agricultural extension program to calculate the t values obtained 0.547 and 1.71 t table (t calculated <t table). The test results with the t test for the number of dependents significantly affect the implementation of agricultural extension program to calculate the t values obtained 3.205 and 1.71 t table (t count> t table). The analysis of different test average of 8.095 and obtained t count obtained t t table table 1.70, this means that there are differences in the implementation of agricultural extension program among female farmers with male farmers.Keyword: women farmers, agricultural extension, the role of women